Epidemiology of invasive aspergillosis and azole resistance in patients with acute leukaemia: the SEPIA Study - Köhler, Philipp; Buchheidt, Dieter (International journal of antimicrobial agents, 2017)
Invasive aspergillosis (IA) is a serious hazard to high-risk haematological patients. There are increasing reports of azole-resistant Aspergillus spp. This study assessed the epidemiology of IA and azole-resistant Aspergillus spp. in patients with acute leukaemia in Germany. A prospective multicentre cohort study was performed in German haematology/oncology centres. The incidence of probable and proven aspergillosis according to the revised EORTC/MSG criteria was assessed for all patients with acute leukaemia [acute myeloid leukaemia (AML) and acute lymphoblastic leukaemia (ALL)]. Cases were documented into a web-based case report form, and centres provided data on standards regarding prophylactic and diagnostic measures. Clinical isolates were screened centrally for azole resistance and, if applicable, underlying resistance mechanisms were analysed. Between September 2011 and December 2013, 179 cases of IA [6 proven (3.4%) and 173 probable (96.6%)] were diagnosed in 3067 patients with acute leukaemia. The incidence of IA was 6.4% among 2440 AML patients and 3.8% among 627 ALL patients. Mortality at Day 84 was 33.8% (49/145) and attributable mortality was 26.9% (39/145). At Day 84, 53 patients (29.6%) showed a complete response, 25 (14.0%) a partial response and 17 (9.5%) a deterioration or failure. A total of 77 clinical Aspergillus fumigatus isolates were collected during the study period. Two episodes of azole-resistant IA (1.1%) were caused by a TR/L98H mutation in the cyp51A gene. With only two cases of IA due to azole-resistant A. fumigatus, a change of antifungal treatment practices in Germany does not appear warranted currently.